HPLC Determination of Valdecoxib from Pharmaceutical Formulation - Baviskar, D.T.; Girase, N.O.; Deshpande, A.Y.; Sane, R.T.; Sharma, R.B.; Jain, D.K. (Asian Journal of Chemistry, 2010)
Present method describes high performance liquid chromatographic determination of valdecoxib from pharmaceutical formulations by using rofecoxib as an internal standard. The separation was carried out on cosmosil octadecyl silane (C18) (150 mm × 4.6 mm, i.d.) 5 μ column. The mobile phase was comprised of ammonium acetate buffer:acetonitrile in the volume ratio of (55:45 ) (v/v) with 0.1 % triethylamine. The detection and quantification was carried out using a UV-visible detector at 239 nm. Linear concentration range of valdecoxib was observed to be 0.30- 100.00 μg mL-1. The developed method was validated to determine its accuracy, precision, specificity and stability by carrying out recovery, linearity, specificity and stability experiments. The method developed is simple, fast, accurate and precise and hence can applied for routine quality control analysis of valdecoxib from pharmaceutical formulation and for stability studies.